Recommendations for the use of Japanese encephalitis vaccines - Ping-Ing Lee; Yhu-Chering Huang; Kao-Pin Hwang; Ching-Chuan Liu; Cheng-Hsun Chiu; Po-Yen Chen; Chun-Yi Lu; Chih-Jung Chen; Luan-Yin Chang; Nan-Chang Chiu; Hsin Chi; Hsiao-Chuan Lin; et al. (Elsevier, 2020)
Japanese encephalitis (JE) is a mosquito-borne viral infection which is prevalent in Taiwan. The virus circulates in an enzootic cycle in pigs which serve as amplifying hosts. Outbreaks typically occur during summer. A universal vaccination program using 4-shot mouse brain-derived inactivated vaccine has successfully controlled JE epidemics in Taiwan since 1968. More than 90% of JE cases in recent years were older than 20 years in Taiwan. Because of several drawbacks, mouse brain-derived vaccine has been replaced by newer generation JE vaccines, including inactivated Vero cell-derived vaccine and live chimeric vaccine. The present article describes the recommendations in Taiwan for the use of new JE vaccines and the schedules for shifting between different JE vaccines. Key Words: epidemiology, immunization schedule, Japanese encephalitis, vaccination